2018
DOI: 10.1186/s12884-018-1898-7
|View full text |Cite
|
Sign up to set email alerts
|

“Well, not me, but other women do not register because...”- Barriers to seeking antenatal care in the context of prevention of mother-to-child transmission of HIV among Zimbabwean women: a mixed-methods study

Abstract: BackgroundWhile barriers to uptake of antenatal care (ANC) among pregnant women have been explored, much less is known about how integrating prevention of mother-to-child transmission (PMTCT) programmes within ANC services affects uptake. We explored barriers to uptake of integrated ANC services in a poor Zimbabwean community.MethodsA cross-sectional survey was conducted among post-natal women at Mbare Clinic, Harare, between September 2010 and February 2011. Collected data included participant characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…One commonly cited other factor was husband’s education and employment, where women whose partners had higher levels of education or formal employment had increased usage of ANC [ 38 ]. Unwanted pregnancies [ 45 , 73 , 76 ], stigma from the community or family members [ 36 , 50 , 74 ], community members advising against using formal ANC services [ 21 , 77 ], use of traditional healers [ 47 , 77 ], lack of awareness and knowledge [ 31 , 38 , 78 , 79 ] and performance-based financing interventions [ 80 , 81 ] were additional factors associated with delayed and less frequent use of ANC.…”
Section: Resultsmentioning
confidence: 99%
“…One commonly cited other factor was husband’s education and employment, where women whose partners had higher levels of education or formal employment had increased usage of ANC [ 38 ]. Unwanted pregnancies [ 45 , 73 , 76 ], stigma from the community or family members [ 36 , 50 , 74 ], community members advising against using formal ANC services [ 21 , 77 ], use of traditional healers [ 47 , 77 ], lack of awareness and knowledge [ 31 , 38 , 78 , 79 ] and performance-based financing interventions [ 80 , 81 ] were additional factors associated with delayed and less frequent use of ANC.…”
Section: Resultsmentioning
confidence: 99%
“…The current study also upon controlling for confounders indicates that religion had no significant association with late ANC attendance. Other studies in South African and Zimbabwe suggest that culture and religion influence ANC attendance and that the practices attached to these beliefs tend to delay ANC initiation [20] [21].…”
Section: Association Between Socio-demographics and Late Anc Seeking mentioning
confidence: 95%
“…However, the literature is more mixed regarding user fees. Some studies suggest women are willing to financially contribute to their stay at a MWH, while others suggest that user fees will impede access, especially for the poor ( Borghi et al., 2006 ; Sibanda et al., 2018 ). A qualitative study based on the gathered perspectives of pregnant women, mothers, health care workers, and community members showed that participants at MWHs express a concern that women will be deterred by user fees because other reproductive health services have been free in Zambia since 2006 ( Chibuye et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review regarding drivers and deterrents of facility-based delivery in sub-Saharan Africa found that women with high household wealth and high socioeconomic status were more likely to use facility-based delivery ( Moyer and Mustafa, 2013 ). High fees have also been identified as barriers to access antenatal and postnatal care services ( Sacks et al., 2017 ; Sibanda et al., al.,2018 ). Consequently, the low utilisation of key reproductive health services contributes to the high maternal mortality and morbidity that are fundamentally preventable in LICs ( Sacks et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%